Repetition of Therapeutic Pinning By a Mentally Challenged: A Case Report and a Medico-Legal Lesson Learnt from Kathmandu Medical College and Teaching Hospital, Kathmandu, Nepal - Barnawal, Siddhartha; Acharya, Jenash (Birat Journal of Health Sciences, 2018)
We present an unusual case of a 27 year-old-female with undiagnosed mental illness who presented with pricking type of tenderness in and around umbilicus and lower left quadrant of left breast. X-ray revealed the presence of sewing needles on those areas. The foreign body was inserted deliberately by the patient herself on trying to mimic the FNAC procedure performed on her a day before. Under C-arm guidance both the needles were located and extracted. Insertion of foreign body via abdominal wall is the first published report to our knowledge. Performing an invasive procedure in front of a mentally challenged individual requires precaution as a clinician, is an important lesson learned. Birat Journal of Health SciencesVol.2/No.3/Issue 4/Sep- Dec 2017, Page: 303-305